Stepchildren of the shtetl: the destitute, disabled, and mad of Jewish Eastern Europe, 1800-1939 - Meir, Natan M. (Stanford studies in Jewish history and culture, 2020)
"Stepchildren of the Shtetl considers marginal peoples in East European Jewish society and culture--the disabled, mentally ill, and indigent--and how stereotypes and self-perceptions of Jewish marginality have in turn shaped modern Jewish culture, society, and politics"--